Tipe Perkawinan dan Partisipasi Kerja Perempuan - Jamalludin, Jamalludin (Politeknik Statistika STIS, 2024)
Married women have many considerations when deciding to participate in the labor market. Gender norms that provide certain stereotypes often hinder married women from working. A woman's decision to work is closely related to the characteristics of her life partner. The type of marriage cannot be separated from individual preferences and applicable social norms. This paper analyzes the relationship between marriage type and women's work participation. 2017 SPTK data is the main data source in this research. The unit of analysis in this research is married women with 26,947 observations. The classification of marriage types in this research refers to educational assortative marriage, namely high-education homogamy, low-education homogamy, hypergamy, and hypogamy. Descriptive analysis shows that the majority of women have a low education homogamous marriage type, and participate actively in the labor market. Binary logit analysis shows that hypogamous marriages tend to provide the highest opportunities for women to enter the labor market. Higher education strengthens women's bargaining position in the household in making decisions to work.